2011
DOI: 10.1007/bf03325318
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa in the general population: A preliminary screening using a self-administered questionnaire (ORTO-15)

Abstract: The results of this study highlight the diffusion of Orthorexia which may constitute an important risk factor for mental and physical health, but also the opportunity of more specific diagnostic instruments, so to facilitate a thorough understanding of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
97
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 6 publications
20
97
1
12
Order By: Relevance
“…Importantly, these groups were comparable in age, education, and estimated intellectual functioning (all p-values = ns). Although the gender ratio was imbalanced, χ 2 (1) = 11.67, p < 0.001, the high preponderance of women in the ON + group is consistent with other reported samples [22,23].…”
Section: Analyses Between Groupssupporting
confidence: 78%
See 1 more Smart Citation
“…Importantly, these groups were comparable in age, education, and estimated intellectual functioning (all p-values = ns). Although the gender ratio was imbalanced, χ 2 (1) = 11.67, p < 0.001, the high preponderance of women in the ON + group is consistent with other reported samples [22,23].…”
Section: Analyses Between Groupssupporting
confidence: 78%
“…Within the full sample, the 21 participants (20 women) who met the Donini et al threshold for ON [9] were assigned to the orthorexic group (ON + ), a prevalence rate comparable to what Ramacciotti et al (2011) found in their community sample [22]. Another 21 participants (10 women) with the highest ORTO-15 total scores formed a non-orthorexic reference group (ON − ).…”
Section: Analyses Between Groupsmentioning
confidence: 99%
“…The questionnaire, translated in several languages [16][17][18][19], seems to be the most widely used test in the literature to evaluate this behaviour and was the only available tool to measure this phenomenon at the time when data were begun to be collected. Authors [15,20] have proposed different cut-offs (i.e. \35, \40) but an ORTO-15 \ 35 ensures the best predictive capability to correctly identify ON through the highest sensitivity (86.5 %), specificity (94.2 %), and negative predictive value (91.1 %) among the tested cut-offs.…”
Section: Evaluation Of Orthorexia Nervosamentioning
confidence: 98%
“…Obsessions with one's diet or for choosing foods solely for “health” aspects, has given rise to a new form of eating disorder termed “orthorexia nervosa.” As distinct from other eating disorders focused on quantity of food, orthorexia nervosa occurs where the individual is overly concerned about the quality or health aspects of the food they consume . A prevalence of 7%‐58% has been described in the general population, and this may be higher in the FBD population. The restrictive nature of diets used for management of gastrointestinal symptoms, which classify foods into safe and unsafe based on their likelihood to effect symptoms, leads to concern that dietary therapies may intensify the prevalence of this disordered eating behavior.…”
Section: Safety Issues Related To Dietary Therapies In Irritable Bowementioning
confidence: 99%